Effect of Impacted Mandibular Third Molar on Development of Distal Caries of Second Molars - Faiqa Iqbal, Khadija Zia, Ramsha Sajid, Amna Nauman Khan, Sarah Rabbani, Nauman Rauf Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: The aim of this study was to evaluate the incidence of caries on distal aspect of mandibular second molars due to impacted third molars. Methodology: Radiographs were obtained for the patients with clinical evidence of impacted 3rd molar. Dental records including number of impacted third molars, pathological conditions and complaints of caries, pericoronitis and recurrent pain were taken. Data of patients with visible distal caries to second molars in the absence of third molar was also recorded entered into specially formulated Performa. Results: A total of 151 participants shared their data for research purpose. According to Winter’s classification, 42.4% and 41.7% impactions were mesioangular and vertical 3rd molars respectively. According to Pell and Gregory classification more than half (55%) of the impacted 3rd molars were in Class I relationship to the ramus whereas 51% of impacted 3rd molars were at the depth of level A. Conclusion: Caries of second more is more common if the impacted third molar tooth is mesioangulated, having class I relationship with respect to ramus.